2000
DOI: 10.1016/s0960-9822(00)00361-4
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA interference shows that Engrailed controls the synaptic specificity of identified sensory neurons

Abstract: The transcription factor Engrailed (En) controls the topography of axonal projections by regulating the expression of cell-adhesion molecules [1] [2] [3] [4] but it is not known whether it also controls the choice of individual synaptic target cells. In the cercal sensory system of the larval cockroach (Periplaneta americana), small numbers of identified wind-sensitive sensory neurons form highly specific synaptic connections with 14 identified giant interneurons [5] [6], and target-cell choice is independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 18 publications
2
42
0
1
Order By: Relevance
“…En regulates the development of some spinal cord interneurons (Wenner et al, 2000;Simon et al, 2001) and affects the survival of dopaminergic midbrain neurons (Simon et al, 2001;Sgadò et al, 2006). In Drosophila and grasshopper CNS, En controls neuron/ glia fate decisions, neuronal identity, and axon pathfinding (Condron et al, 1994;Lundell et al, 1996;Joly et al, 2007), whereas in cockroach mechanosensory neurons we showed that it also controls axon guidance, synaptic target recognition, and, as a result, escape behavior (Marie et al, 2000(Marie et al, , 2002Marie and Blagburn, 2003;Blagburn and Bacon, 2004;Booth et al, 2009).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…En regulates the development of some spinal cord interneurons (Wenner et al, 2000;Simon et al, 2001) and affects the survival of dopaminergic midbrain neurons (Simon et al, 2001;Sgadò et al, 2006). In Drosophila and grasshopper CNS, En controls neuron/ glia fate decisions, neuronal identity, and axon pathfinding (Condron et al, 1994;Lundell et al, 1996;Joly et al, 2007), whereas in cockroach mechanosensory neurons we showed that it also controls axon guidance, synaptic target recognition, and, as a result, escape behavior (Marie et al, 2000(Marie et al, , 2002Marie and Blagburn, 2003;Blagburn and Bacon, 2004;Booth et al, 2009).…”
Section: Introductionmentioning
confidence: 71%
“…In view of the controlling effect of En on synaptic connectivity in the cockroach cercal system (Marie et al, 2000(Marie et al, , 2002Marie and Blagburn, 2003), we hypothesized that the expression of En could influence the formation of JON synapses with the GF. Therefore, we used the JO15-GAL4 line (Sharma et al, 2002), which is expressed in all of the JO-A and the majority of the JO-B neurons (Kamikouchi et al, 2006;Fig.…”
Section: Ectopic Expression Of En In Jo-b Neurons Causes Them To Nbcomentioning
confidence: 99%
“…En is normally expressed only by neurons born in the medial part of the cercal epidermis (Blagburn et al, 1995). We showed directly that En controls both the axonal arborization and the synaptic connectivity of an identified medial sensory neuron (Marie et al, 2000a; summarized in Fig. 1).…”
mentioning
confidence: 77%
“…The advantage of the technique of RNAi is that it can be easily applied to knock down gene expression and that no extensive knowledge of the genetic make-up of a particular organism is required. The technique of RNAi has already been applied successfully in several insect species (Marie et al, 1999;Lam and Thummel, 2000;Quan et al, 2002;Bettencourt et al, 2002;Blandin et al, 2002;Rajagopal et al, 2002;Valdes et al, 2003;Uhlirova et al, 2003), therefore it holds great promise for the genetic analysis of gene function in insects, in general, including oogenesis.…”
Section: Discussionmentioning
confidence: 99%